Teori Sosiokultural Vygotsky untuk Anak Usia Dini - Eka Kurniati (CV Putra Publisher, 2025)
Lev Vygotsky's sociocultural theory offers a key perspective on young children's development, emphasizing social and cultural interactions in the formation of children's cognition. According to Vygotsky, children's learning cannot be separated from the social and cultural context in which they grow up. Key concepts such as “zone of proximal development” (ZPD) and “scaffolding” underscore the importance of support from more competent adults or slightly more competent peers to help children reach their full potential. ZPD refers to the range between a child's self-achieved and assisted levels of development, while scaffolding indicates the assistance provided by educators or experienced adults to help children learn and develop. In the context of early childhood education, this theory emphasizes the need for activities that involve active social interaction, both in formal and informal education environments, to stimulate the development of language, problem-solving abilities, and other cognitive skills. This research aims to analyze the application of Vygotsky's theory in early childhood education, explore how the social and cultural environment can influence children's learning, and identify pedagogical implications that teachers can apply to best assist children's development. By analyzing educational practices that involve social interactions in children's daily activities, this research will also provide insights into how to create learning environments that support children's cognitive and social development. The results of this study are expected to provide simple recommendations for the development of preschool education curricula that are more responsive to children's social and cultural needs, as well as suggestions for educators on how to optimize learning strategies based on social and cultural interactions.